Organization and geography of global R&D and innovation activities: Insights from qualitative research on leading corporate R&D investors investors - Mafini Dosso; Paulina Ramirez (European Commission, Joint Research Centre (JRC), 2020)
This study examines the on-going structural changes in the international organisation of corporate R&D and innovative (RDI) activities. Insights are mainly drawn from interviews made to innovation representatives and managers of large R&D-investing companies in 2017 in the frame of the European Commission's project - Industrial Research and Innovation Monitoring and Analysis -. The research intends to complement the quantitative evidence available in the project on the worldwide leading corporate R&D investors in order to better characterize the on-going fragmentation of R&D and innovation activities. The study suggests directions for mapping innovation value chains beyond research and inventive activities and carries out important conceptual and policy implications for the configurations and sustainability of innovation systems in Europe.
Keywords: O32; L22; 330; R&D and innovation value chains; MNEs; top R&D investors; interviews; qualitative research